Reseña de actas: Innovación en las prácticas de la enseñanza y la investigación en Ciencias Jurídicas. Desafíos para transversalizar la perspectiva de género(s) y consolidar el derecho antidiscriminatorio, de María Verónica Piccone (comp.) - Espiñeira, Brenda Daiana (2023)
"Piccone, María Verónica (Comp.) (2022), Innovation in teaching and research practices in Legal Sciences. Challenges to mainstream the gender perspective and consolidate anti-discrimination law, 1st ed., Córdoba, Sociedad Argentina of Legal Sociology, Digital book, ISBN 978-987-25475-3-0". -- "In the work reviewed here ... the papers presented and debated within the framework of the "First Conference on innovation in teaching practices and research in Legal Sciences come together. Challenges to mainstream the gender perspective and consolidate the anti-discrimination right" that were organized during the month of November 2020 jointly by the Law School of the School of Humanities and Social Studies of the National University of Río Negro and the Argentine Society of Legal Sociology"